2020
DOI: 10.1016/j.pedneo.2019.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study: Evaluation of potential drug–drug interactions in hospitalized pediatric patients

Abstract: drug-drug interactions; medication errors; pediatric patients; potential drug-drug interactions Purpose: Evaluate the type and severity of potential drug-drug interactions and identify risk factors involved, in pediatric patients admitted in a hospital setting. Methods: Transversal retrospective analytical study was carried out with hospitalized pediatric patients from a Hospital in the West of Mexico, second and third level. The patients included were 18 years old hospitalized in the children wards; those adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
17
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 21 publications
8
17
2
1
Order By: Relevance
“…As expected, the result of logistic regression analysis showed that polypharmacy (more than 3 medications per prescription) was a risk factor for the occurrence of pDDIs, which was in agreement with the pilot study of hospitalized pediatric patients conducted by Fabiola Medina-Barajas et al [ 4 ]. Several studies had drawn a consistent conclusion that the increasing amount of medications was a risk factor for presenting drug interactions [ 24 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As expected, the result of logistic regression analysis showed that polypharmacy (more than 3 medications per prescription) was a risk factor for the occurrence of pDDIs, which was in agreement with the pilot study of hospitalized pediatric patients conducted by Fabiola Medina-Barajas et al [ 4 ]. Several studies had drawn a consistent conclusion that the increasing amount of medications was a risk factor for presenting drug interactions [ 24 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several factors contribute to the occurrence of DDIs in populations, such as age, comorbidities, polypharmacy, nutritional status, and genetic constitution of an individual [3,4]. Therefore, DDIs are of concern especially in elderly patients with comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Profile of children in intensive care unit included in this study (mean age, subtle male predominance, respiratory diseases as the principal cause of hospitalization) confirmed the findings of other national and international researches (Corullón, 2007;Vonbach et al, 2008;Ferreira et al, 2012;Lanetzki et al, 2012;Alves et al, 2014;Medina-Barajas et al, 2020). However, the mean length of hospital stays of children in the ICU (11.3 days) was longer than that observed in other Brazilian hospitals, which ranged from 5.5 to 10.6 days (Corullón, 2007;Molina et al, 2008;Lima and Cassiani, 2009;Ferreira et al, 2012;Alves et al, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…The incidence observed in this study (70%) was similar to findings in PICU of United States children hospitals (75%) and another Brazilian PICU (72%) (Lima and Cassiani, 2009;Dai et al, 2016). Other studies found lower frequencies in Indian (63%), Pakistani (59.4%), Mexican (42%), Chilean (41%) PICUs (Santibáñez et al, 2014;Ismail et al, 2017;Rao et al, 2019;Medina-Barajas et al, 2020). An investigation at a Brazilian neonatal intensive care unit found a pDDI prevalence equal to 51% (Queiroz et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…Ahmed et al also reported that out of 800 prescriptions, 290 have at least one drugdrug interaction (36.25%) [21]. Medina-Barajas et al reported that most of the interactions in their study were minor [22]. They also stated that about 42% of the patients presented some degree of potential drug-drug interactions [22].…”
Section: Resultsmentioning
confidence: 98%